Hydrogen Sulfide Inhibits Ferroptosis in Cardiomyocytes to Protect Cardiac Function in Aging Rats - Liang, Zihui; Miao, Yuxin; Teng, Xu; Xiao, Lin; Guo, Qi; Xue, Hongmei; Tian, Danyang; Jin, Sheng; Wu, Yuming (Frontiers in Molecular Biosciences, 2022)
Aging contributes significantly to cardiovascular diseases and cardiac dysfunction. To explore the reasons for the decline in cardiac function in the elderly, we collected clinical data and blood samples from 231 individuals. Our results indicated that aging was accompanied by a decline in cardiac function and remodeling of the left ventricle, and cardiac function was negatively correlated with age. Serum hydrogen sulfide (H2S) decreased, while serum malondialdehyde (MDA) and iron increased with aging in healthy individuals. A rat model of aging and iron overload was constructed for in vivo research. In the animal model, we found that the expression of endogenous H2S-producing enzymes decreased, and endogenous H2S levels decreased, while oxidative stress levels rose. The regulation of iron metabolism and the maintenance of iron homeostasis declined. The accumulation of MDA and iron led to ferroptotic cell death and subsequent myocardial injury and deterioration. A high-iron diet accelerated the aging process and death in rats. The decline of cardiac function in aging rats and iron-overload rats may be caused by cardiomyocyte ferroptosis. Exogenous H2S enhanced the expression of endogenous H2S synthase, promoted endogenous H2S production, regulated iron metabolism, and reduced oxidative stress levels. The protective effects of H2S on cardiac function in aging rats and iron-overload rats may be partly due to the inhibition of cardiomyocyte ferroptosis. We demonstrated that cardiac dysfunction associated with aging was closely related to decreased endogenous H2S levels and cardiomyocyte ferroptosis. H2S-regulated iron metabolism reduced oxidative stress levels in cardiomyocytes, inhibited cardiomyocyte ferroptosis, and protected cardiac function in aging rats.